2020
DOI: 10.4209/aaqr.2020.05.0218
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying a Possible Relationship between COVID-19, Air Quality and Meteorological Factors: Evidence from Kuala Lumpur, Malaysia

Abstract: Air pollution is the culprit to yearly millions of deaths worldwide, deteriorating human health. What is not yet clear is the impact of environmental factors on susceptibility to getting infected by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The study aimed to determine associations between air quality, meteorological factors, and COVID-19 cases in Kuala Lumpur, Malaysia. Air pollutants and meteorological data in 2018-2020 were obtained from the Department of Environment Malaysia, while dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
82
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(103 citation statements)
references
References 28 publications
17
82
2
2
Order By: Relevance
“…Similar to the present study reduction in PM10, PM2.5, NO2, CO and SO2 levels and a significant enhancement in O3 is observed at Iran, China, Kazakhstan, Singapore, Morocco, Brazil, Malaysia and Spain (Table 2) (Broomandi et al, 2020;Chen et al, 2020;Kerimray et al, 2020;Li and Tartarini, 2020;Otmani et al, 2020;Siciliano et al, 2020;Suhaimi et al, 2020;Tobias et al, 2020).…”
Section: Accepted Manuscriptsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to the present study reduction in PM10, PM2.5, NO2, CO and SO2 levels and a significant enhancement in O3 is observed at Iran, China, Kazakhstan, Singapore, Morocco, Brazil, Malaysia and Spain (Table 2) (Broomandi et al, 2020;Chen et al, 2020;Kerimray et al, 2020;Li and Tartarini, 2020;Otmani et al, 2020;Siciliano et al, 2020;Suhaimi et al, 2020;Tobias et al, 2020).…”
Section: Accepted Manuscriptsupporting
confidence: 90%
“…Recent studies reported on short term exposure to air pollution and COVID-19 infection have found significant positive association of air pollutants with COVID-19 confirmed cases (Suhaimi et al, 2020;Zhu et al, 2020). Suhaimi et al (2020) found significant positive association between COVID-19 cases and PM10, PM2.5, CO, NO2 and SO2 pollutants in Malaysia however, Zhu et al (2020) observed positive association between COVID-19 cases and PM10, PM2.5, NO2…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…The neighboring nation of Malaysia reported a national-wide drop of PM 2.5 between 11.3 and 23.7% during 18 March to 14 April 2020 compared to 14 to 17 March 2020 (Abdullah et al, 2020). Suhaimi et al (2020) showed a reduction of PM 2.5 , NO 2 , CO, and SO 2 by 3 to 36%, 43 to 68%, 1 to 48%, and 2 to 48% according to different regions between 18 March and 21 April 2020 in Malaysia (Suhaimi et al, 2020). Nadzir et al (2020) reported that CO concentrations decreases ranging from 40.5 to 47.5%, but PM 2.5 levels showed a both increase and decrease according to different regions in Malaysia during the period from 18 March to 08 April 2020 (Nadzir et al, 2020).…”
Section: Changes In Air Quality In Southeast Asiamentioning
confidence: 99%
“…High concentrations of NO 2 , CO, and SO 2 were also observed in the late evening is generally due to meteorological influence and atmospheric stability (Awang et al, 2000). Nonetheless, highest concentrations of PM 2.5 , NO 2 , and CO were found in urban stations which it is highly possible that these concentrations are from vehicular emissions (Mohd Nadzir et al, 2020;Suhaimi et al, 2020). Although there was change in daily activities during MCO, similar diurnal patterns were observed; however, significant lower readings were observed in all settings.…”
Section: Temporal and Spatial Variations Of Air Pollutantsmentioning
confidence: 97%
“…However, the study also reported an increase in PM 10 and PM 2.5 concentrations in one of their monitoring stations due to the transport emissions from other regions, local burning activities, and the highway construction nearby. A study by Suhaimi et al (2020) showed that PM 10 , SO 2 , NO 2 , and CO concentrations were reduced between 5 and 50% on the first week of MCO in urban setting. Also, a study by Kanniah et al (2020) revealed that the highest reductions were observed in NO 2 concentrations in Malaysian urban region.…”
Section: Introductionmentioning
confidence: 99%